The Use of Multiple Pin and Methylmethacrylate External Skeletal Fixation for the Treatment of Orthopaedic Injuries in the Dog and Cat - Ross, J. T.; Matthiesen, D. T. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
Multiple pin and methylmethacry-late external fixation devices were applied in 74 animals to successfully treat several different types of orthopaedic injuries. The major advantages associated with use of the technique included increased versatility in the location and angle of fixation pin place-ment and greater ease in placement of the connecting bar when compared with conventional clamp and connecting bar systems, particularly with transarticular placement of a device. The major disadvantages associated with the technique included, increased difficulty compared to conventional K-E systems regarding postoperative adjustment of the device and difficulty in removing individual pins that were loose or infected. Generally, removal of the device was not a problem, provided sufficient space was left between the connecting bar and the skin surface.Complications associated with the technique were similar to studies which have evaluated other types of external fixation and include fixation pin loosening, pin tract drainage or infection, fixation failure, osteomyelitis, angular limb deformity, mal-union, delayed union and nonunion.The multiple pin and methylmethacrylate external fixator provides a useful and effective method of repair for a wide variety of orthopaedic injuries. The use of methylmethacrylate as a connecting bar is a helpful adjunct to standard external fixation systems.The use of multiple pin and methylmethacrylate external fixation (MPMF) increases the versatility of the external fixation technique in small animal orthopaedic injuries. Disadvantages include difficulty in removing or replacing individual fixation pins.
Keywords: External fixation; fracture repair; methylmethacrylate